1991
DOI: 10.1016/0020-7292(91)90767-y
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial lesions in patients undergoing tamoxifen therapy

Abstract: OBJECTIVE: To evaluate endometrial alterations by means of transvaginal ultrasound and to correlate them with hysteroscopic and histological findings in patients under tamoxifen therapy. MATERIALS AND METHODS: The present study was developed in the period between January 2003 and December 2005, including patients under tamoxifen therapy for breast cancer, and presenting with endometrial thickening > 5 mm. The sonographic findings were correlated with hysteroscopic and anatomopathological results. RESULTS: Twen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
42
0
2

Year Published

1995
1995
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(50 citation statements)
references
References 7 publications
5
42
0
2
Order By: Relevance
“…There have been many reports of abnormalities identified in the endometrium in women on tamoxifen including hyperplasia with atypia and polyps, some of which are similar to the changes seen with ERT (Cross and Ismail, 1990;Neven et al, 1990;De Muylder et al, 1991;Cohen et al, 1993;Lahti et al, 1993;Neven, 1993;Ismail, 1994;Aleem and Predanic, 1995).…”
mentioning
confidence: 92%
“…There have been many reports of abnormalities identified in the endometrium in women on tamoxifen including hyperplasia with atypia and polyps, some of which are similar to the changes seen with ERT (Cross and Ismail, 1990;Neven et al, 1990;De Muylder et al, 1991;Cohen et al, 1993;Lahti et al, 1993;Neven, 1993;Ismail, 1994;Aleem and Predanic, 1995).…”
mentioning
confidence: 92%
“…Nowadays, more than 1 in 20 female cancers in Europe are of the endometrium. [1][2][3][4][5][6][7][8][9][10] Contrary to cervical carcinoma, no screening programs have been organized for the early detection of endometrial adenocarcinoma. The lack of screening programs may be related to the precocious presenting symptoms and to the relative good prognosis of the majority of endometrial adenocarcinomas.…”
mentioning
confidence: 99%
“…[2][3][4][5][6][7] In postmenopausal women tamoxifen exerts a proliferative effect on the endometrium, as measured by the hyperdiploid fraction, 8 and clinical studies have reported an increased incidence of endometrial polyps and hyperplastic endometrial changes, mostly interpreted as evidence of the agonistic effect of tamoxifen. [9][10][11][12][13][14] Histology of tamoxifen exposed postmenopausal endometrium in general shows a characteristic picture of a condensated, hypercellular, collagen rich stroma, whereas the glandular epithelium stays thin and atrophic or metaplastic, the flattened epithelium lining cystically dilated glands or polyps. 8 13 15 The incidence of benign, tamoxifen induced changes by far exceeds the incidence of endometrial cancer, 14 suggesting that most of these endometrial changes do not progress to cancer.…”
mentioning
confidence: 99%